Occupational therapy return to work interventions for persons with trauma and stress-related mental health conditions: A scoping review. - Edgelow, Megan; Harrison, Laura; Miceli, Meghan; Cramm, Heidi (Work, 2020)
BACKGROUND: Trauma and stress-related mental health conditions can impact a person's ability to participate in work and can cause disruptions in employment. Best practice guidelines for occupational therapy return to work interventions with these populations are limited. OBJECTIVE: To identify and describe occupational therapy return to work interventions for trauma and stress-related mental health conditions. METHODS: Using a scoping review methodology, research databases were searched for papers relating to occupational therapy, return to work interventions, and trauma and stress-related mental health conditions. Three reviewers independently applied selection criteria and systematically extracted information. Data were extracted and synthesized in a narrative format. RESULTS: The search produced 18 relevant papers. The interventions described were more often person-focused versus environment- and occupation-focused, and many were carried out by multidisciplinary teams, making it difficult to identify best practices for occupational therapists in this area. CONCLUSION: Emerging practices include the Swedish "ReDO" intervention, support for active military members to manage operational stress to remain at work, and multidisciplinary team treatment. Further research, including studies with direct focus on the implications of occupational therapy interventions for return to work with trauma and stress-related mental health conditions, is required.